PENGARUH LAMA PERENDAMAN KUPANG (Musculita senhausia) DALAM SARI BELIMBING WULUH (Averrhoa bilimbi) TERHADAP KADAR LOGAM BERAT Pb - Apt, Sudirman (Universitas Muhammadiyah Surabaya)
PENGARUH LAMA PERENDAMAN KUPANG (Musculita senhausia) DALAM SARI BELIMBING WULUH (Averrhoa bilimbi) TERHADAP KADAR LOGAM BERAT PbÂ Drs. Sudirman, AptProdi D3 Analis Kesehatan UM SurabayaAbstractÂ Kupang is one category of animals with complete protein that has a high tolerance for concentrations of certain metals that can accumulate heavy metals than other animals, one of the heavy metals that can be accumulated by mussels body is lead (Pb). Starfruit has antioxidants that can bind to the levels of Pb in Pb in mussels mussels that can be reduced. The formulation of this research is there any effect of soaking mussels in cider starfruit on levels of lead (Pb)? The purpose of this study was to determine the effect of starfruit juice on levels of Pb in mussels, to analyze laboratory Pb levels in mussels without giving starfruit juice, and to analyze laboratory Pb levels in mussels by giving starfruit juice. Type of research is experimental. The samples analyzed were mussels mussels sold by traders in the Market Village Kenjeran Sukolilo Bulak district, a total of 6 samples obtained from 7 merchants. Traders - traders were selected at random from 7 vendors selling mussels. Taking mussels each merchant mussels sampled as many as 1 in order to obtain the number of 6 samples. Of 6 samples obtained such that each - each sample to get 4 treatments, ie the one without treatment and the three treated (soaked in cider starfruit with immersion length variation). From the results of examination by using Graphite Furnace Atomic Absorption Spectrophotometer obtained average - average levels of Pb in mussels without soaking the starfruit juice at 12.35 ppm, and after soaking in starfruit juice Pb levels in mussels, marinated for 30 minutes, 60 minutes , and 90 minutes respectively - were in the amount of 8.04 ppm, 4.67 ppm, and 3.79 ppm. Statistical analyzes Anova test showed the influence of duration of immersion in starfruit juice on levels of Pb in mussels with significance level (P) 0.000 where the value is less than 0.05.Â Keyword : Kupang (Musculita senhausia), Averrhoa bilimbi, lead (Pb)